Carcass and Non-Carcass Production of Local Sheep with Age Variations and Slaughter Weight in Yogyakarta City - Andri Haryono Awalokta Kusuma; Adib Norma Respati; Putri Awaliya Dughita (Journal of Livestock Science and Production, 2020)
The study was aimed to determine the influence of age and slaughter weight on carcass and non-carcass (head, skin, and digestive tract) of local sheep. Sixty local sheeps consisted of thirty local female sheep with slaughter weight 15-19,99 kg and thirty local sheeps with slaughter weight 20-25 kg, consisted of age less than one year, 1-1,5 years, and 2- 3 years. Data collected included age, slaughter weight, carcass weight, non-carcass (weight of head, skin, and digestive tract), carcass percentage, and non-carcass percentage. Data were analyzed in a 2 x 3 factorial design. The first factor was slaughter weight and the second factor was the age of local sheep. The difference between means was analyzed using Duncan’s Multiple Range Test (DMRT). The results showed that slaughter weight significantly(P<0.05) influenced carcass and non-carcass percentage. Age of local sheep significantly (P<0,05) influenced carcass percentage, skin percentage, and digestive tract percentage. Therefore it could be concluded that the slaughter weight significantly influenced carcass and non-carcass and age significantly influenced carcass and non-carcass percentage, except legs percentage. In conclusion, age dan body weight gave to increase the percentage of carcass dan non-carcass. There was no interaction between the age of local sheep and slaughter weight on the carcass and non-carcass percentage.Keywords: Local sheep, slaughter weight, age, carcass, non-carcass